La política migratoria del Estado ecuatoriano y los actuales enfoques sobre la movilidad humana - Narváez Castillo, Santiago Xavier (2024)
The general objective of the research was to determine the relevance of the migration policy in Ecuador, analyzing both the relevant regulations in force to understand the legal situation of migrants, and the approach of the Ecuadorian State in matters of human mobility, within the framework of the Constitution. and the Human Mobility Law, to safeguard the rights of migrants, including protection, health, education, and free mobility. Despite the progress, challenges were identified such as adapting legislation to changing migratory dynamics and facing massive flows such as that of Venezuelan migrants. The research is relevant given global human mobility and Ecuador's specific challenges, especially with the recent arrival of Venezuelan migrants. In addition, the coherence of national policies with international human rights standards and their ability to adapt to migratory dynamics was evaluated, finding that Ecuador has a robust regulatory framework\; but it faces challenges in its implementation and application, highlighting the need to adapt legislation and prepare to manage massive migratory flows. The approach used was qualitative and the methods applied were socio-legal and normativist. In any case, in this work a normativist approach was evident in Ecuador's immigration policy\; especially, in terms of human rights\; However, this approach has had to face the various situations and challenges that arise in its practical implementation.